Science and Technology Agreements in the Toolbox of Science Diplomacy: Effective Instruments or Insignificant Add-ons? - Nicolas Rüffin (Institute for European Studies, 2017)
- Both practitioners and scholars tend to regard Science and Technology Agreements (STA) to be important, prominent, and highly effective tools for science diplomacy (SD). Yet it is far from clear whether they form an integral part of strategic approaches toward SD or mostly remain rather erratic ad-hoc agreements with more probably vague or even insignificant roles. Since we know but little about the development of STA over time, it is very difficult to get data and a valid picture on what is going on there at all and what impact STA might have. - Based on a working definition of STA, we conducted a quantitative study to map the STA that six countries (DK, FR, DE, CH, UK, U.S.) and the European Union have signed between 1961 and 2016. In addition, through a range of expert interviews, we tried to capture practitioners' views on the role and workings of STA in the realms of international science policy and SD in particular. - What we see is a large increase in the number of concluded STA over time. While some of the countries in our sample made extensive use of STA, others were more hesitant or even reluctant to do so. Still, we witness a strong integration of G20-states in a network of bilateral STA. To illustrate the highly diverse uses and importance of STA, we present four cases of negotiations that point to their limited strategic use. From our expert interviews, we could differentiate between four types of views or opinions with regard to the uses of STA. - If we view STA in their respective political context, some apparently erratic provisions turn into meaningful strategic instruments. Overall, STA may carry different meanings to different stakeholders engaged in the negotiations; this is why they always serve as boundary objects. - For future research, it would be worthwhile to look into the interconnections, or interplays, between STA and other tools of SD on the one hand and contextual variables like geopolitical shifts and organisational backgrounds that shape negotiations and appraisal of STA on the other.
Keywords: 300; Science and Technology Agreement; STA; science diplomacy; European Union; Denmark; France; Germany; Switzerland; United Kingdom; United States